Student-Athletes Perceptions on the LGBTQIA+ Member Inclusion in Gender- specific Sports in the Philippine Educational System - Kimverly D. Gamutin; Jamaeca D. Acero; El Shaine P. Macarandan; Christine Dianne G. Varron; Louie Gula (Diversitas Journal)
This study explored and analyzed the perceptions of students' athletes regarding LGBTQIA+ inclusion in gender-specific sports in the Philippine Educational System. In order to better understand the perceptions of student-athletes from about LGBTQIA+ participants in any gender-specific sports, we used structured interviews. This study was led by a qualitative methodology, especially a phenomenological research design. Phenomenology is a qualitative research method that is ultimately suitable for gaining a thorough understanding of the effective process that describes the informant's life experiences. Through this design, we investigated how student athletes perceived the inclusion of LGBTQIA+ people in gender-specific sports from various perspectives. This study comes up different results, Inclusion and Acceptance of LGBTQIA+ Individuals in Sports, Gender-Inclusive Practices and Competence in Sports, Mitigating Gender Identity Discrimination, Identity Expression, and Comfort in Sports, Equality and Equity in Training Regardless of Identity, Gender Identity in Sports, Absence of Gender Identity-Based Exclusions and Inclusion Efforts. In conclusion, having a member who identifies as LGBTQIA+ is not a curse nor a blessing because athletes do not find it offensive; instead, it brings them joy at the end of a long day. Athletes contribute what they can because they feel respected by their teammates.